STUDI PENGGALIAN ASPIRASI PEMILIK TOKO DALAM RANGKA PENATAAN KORIDOR JL. GAJAH MADA KOTA DENPASAR - Acwin Dwijendra, Ngakan Ketut; Yudantini, Ni Made (Jurnal Natah; Vol. 5, No. 2 Agustus 2007, 2012)
The coridor of Gajah Mada street has a potency of historical and economi value which need urgently to be conserved. The growth of development in this neighbourhood has created the dilapidation both physical and environment matter. Based on that, Local Government of Denpasar has considered that it is very crucial to initiate design of this coridor by fully supporting the wholeseller as the owner of region. Through corporation between Researh Institution of Udayana University and Government of Denpasar, they accomplish the study of aspiration exploration to the wholeseller in order to obtain opinion to the design of coridor and also to develop the sense of belonging of them to this area. By means of questionnaire, interview and focus group discussion among stakeholders, the study results presented that the wholeseller require the planning of central parking, the comportable pendestrain ways, landscape greening, public toilet, loading-unloading, shuttle bus, signage, lighting arrangement and other street furniture.
Keywords: aspiration exploration, wholesaler, design of coridor.